PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP PROFESIONALISME GURU DI MA SE-KECAMATAN TIGARAKSA - Achmad Fadhliluddin Ginanjar; Siti Zubaidah; Rian Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of transformational leadership style, job satisfaction, and Organizational Citizenship Behavior (OCB) on teacher professionalism in Madrasah Aliyah (MA) throughout Tigaraksa District. The study employed a quantitative approach using a survey method. The population consisted of 180 teachers, with a sample of 124 teachers selected through proportional random sampling. Data were collected through questionnaires using a five-point Likert scale. Data analysis included classical assumption tests consisting of normality, linearity, and homogeneity tests. Hypothesis testing was conducted using multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results showed that transformational leadership had a positive and significant effect on teacher professionalism with a beta coefficient of 0.211 and a t-value of 3.020, which was greater than the t-table value of 1.980. Job satisfaction also had a positive and significant effect on teacher professionalism with a beta coefficient of 0.265 and a t-value of 4.071, exceeding the t-table value of 1.980. In addition, Organizational Citizenship Behavior (OCB) had a positive and significant effect on teacher professionalism with a beta coefficient of 0.281 and a t-value of 3.146, which was higher than the t-table value of 1.980. Simultaneously, transformational leadership, job satisfaction, and OCB significantly influenced teacher professionalism, as indicated by an F-value of 8.073 and a significance level of 0.000 (< 0.05). The most dominant variable affecting teacher professionalism was OCB, contributing 45.1%, followed by transformational leadership at 28.4% and job satisfaction at 21.7%.